PANDANGAN HAKIM TERHADAP DISPENSASI PERNIKAHAN ANAK DI BAWAH UMUR (Studi Kasus di Pengadilan Agama Kota Malang) - Anita Anita; Ahmad Subekti; Dwi Ari Kurniawati (Jurnal Hikmatina, 2020)
Marriage is an important event in human life because marriage is not only related to the two candidates' personal husband, but also involves family and community affairs, for those who are married must meet certain conditions, one of them is age. If one prospective bride does not meet the specified age requirements, she must file a marriage dispensation at the local Religious Court. Therefore, the researcher conducts research on "the judge's view of the marriage dispensation of minors" in which the researcher examines the case regarding the dispensation of underage marriage at Malang City Religious Court. This description aims to find out about the grounds and considerations of judges in resolving the dispensation of underage marriages, about the factors that cause the dispensation of underage marriages and also the judge's views regarding the underage marriage dispensation of minors. The method used in this case study is a qualitative approach. This type of research is field research where researchers go directly to the location. Data collection tools used by researchers in the form of interviews and documentation and data analyzed with data in the form of data reduction, data presentation and verification. Keywords: The Judge’ s Views, Marriage Dispensation, Underage Marriage.